Improving Project Management Performance in Libya - Strategies and Future Directions (Journal of Human Sciences, 2025)
"Projects of various types are an important building block in the economy of any country in the world. However, these projects, regardless of their types, cannot succeed without wise management based on solid scientific foundations. These foundations can be derived through various scientific studies. Accordingly, this research addresses an important topic in the field of management, which is the management of various projects in the Libyan state. It attempts to observe the reality, identify the most significant difficulties and obstacles affecting project management, and propose important strategies and directions that contribute to improving these projects. The research followed the descriptive-analytical method and concluded with important results in this regard, including that improving project management in Libya can only be achieved through the concerted efforts of all state institutions, both private and public. The research also proposed recommendations that may contribute to the development and improvement of project management."